Clinical informationist educational needs and goals: A scoping review - Mohammadreza Hashemian; Alireza Rahimi; Nikoo Yamani; Peyman Adibi; Firoozeh Zare-Farashbandi (Wolters Kluwer Medknow Publications, 2020)
Clinical informationist (CI) is one of the current trends in the field of medical librarianship and information science. CIs are members of clinical care teams, and their main duty is to fill the gap in the information needs of health-care workers and patients using information sources. They need an official and standard education. This study aims to identify the educational goals and needs of CIs. To this end, a scoping review was conducted using the Preferred Reporting Item for Systematic Reviews and Meta-analyses guidelines. The ISI Web of Science, Scopus, Proquest (MEDLINE), Science Direct, Emerald, ERIC, Cochrane, and Library, Information Science and Technology Abstracts were searched. The Journal of the European Association for Health Information and Libraries was hand searched for relevant studies. A total of 1026 studies were extracted, and 38 studies were selected for the final review. The review resulted in identifying 18 goals in cognitive, emotional, and psychomotor areas. Furthermore, the educational needs were identified in eight educational needs including research method and statistics, education, medical knowledge, information and librarianship science, clinical environment knowledge, evidence-based knowledge, information technologies and systems, management, and leadership. Although part of these educational needs can be met through general medical librarianship and information science education, further specialized education for CIs requires specific aims and curriculum. Thus, the results of this study can be the basis for future studies regarding the competencies of CI in order to provide a more precise and detailed curriculum based on these educational needs.